Study of resource utilization in IEEE 802.15.4 Wireless Body Sensor Network, Part II: Greedy Channel Utilization - Moravejosharieh, Amirhossein; Tabatabaei Yazdi, Ehsan; Willig, Andreas (Proceedings - IEEE International Conference on Networks, 2013)
The channel scarcity phenomenon has recently introduced new challenges in the field of Wireless Body Sensor Networks (WBSNs). Within a WBSN, node's communication is restricted throughout their defined active period. As the number of WBSNs increases, the overlapping active periods are elevated due to inefficient utilization of the spectrum. This consequently results in higher packet loss ratio and eventually performance degradation of the WBSNs entirely. To overcome the aforementioned issue, in this paper, we have proposed a new scheme called "Greedy Channel Utilization" (GCU) scheme in which coordinators compete for slot reservation and attempt to utilize the channel voraciously by pushing other contestants in to sleep mode. To evaluate the performance of our proposed scheme, we compared it with the bare IEEE 802.15.4 Std. in terms of channel utilization percentage, packet loss ratio, sensor's orphan time and energy consumption of sensors and coordinator. Eventually, this study concludes the outperformance of GCU scheme over the blind scheme.